Analisis Kesulitan Belajar Siswa Pada Mata Pelajaran Matematika - Andani Salamah Syakur; Ratih Purnamasari; Dadang Kurnia (FKIP UNIVERSITAS PAKUAN, 2021)
This research was conducted with the aim of analyzing students' learning difficulties in mathematics. Located at the Neglasari State Elementary School, Bogor City, it was held in the even semester of the 2020/2021 Academic Year. In this research, the writer uses qualitative research with descriptive method. The data collection procedure was carried out by triangulation, namely a combination of the results of observations (observations), interviews and documentation. Data were analyzed by reducing irrelevant data, presenting data systematically, and drawing conclusions from research findings. The results showed that the learning difficulties experienced by students in mathematics subjects were difficulties in understanding concepts, difficulties in understanding mathematical language, difficulties in calculations and difficulties in solving problems. It can be concluded that students still have difficulty learning in mathematics. The solution is that students must get the right treatment, with the efforts of teachers who are also supported by their parents, as well as the enthusiasm and motivation of students to improve their numeracy skills.